2016
DOI: 10.1177/0954407016632141
|View full text |Cite
|
Sign up to set email alerts
|

Fuel efficiency analysis and peak pressure rise rate improvement for neat n-butanol injection strategies

Abstract: Engine tests were conducted to investigate the efficiency and the peak pressure rise rate performance of different fuel injection strategies for the direct injection of neat n-butanol in a compression ignition engine. Three different strategies were tested: a single-shot injection; a pilot injection; a post-injection. A single-shot injection timing sweep revealed that early injections had the highest indicated efficiency while late injections reduced the peak pressure rise rate at the cost of a slightly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Other types of alternative fuels are alcohols. The studies on the use of these types of fuels and fuel blends in DEs focus on the use of ethanol, methanol, and 1-butanol. Their use is associated with beneficial ecological effects, especially the limitation of pollutant emissions. ,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Other types of alternative fuels are alcohols. The studies on the use of these types of fuels and fuel blends in DEs focus on the use of ethanol, methanol, and 1-butanol. Their use is associated with beneficial ecological effects, especially the limitation of pollutant emissions. ,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, n-butanol is typically served as blended fuel with gasoline or diesel in order to reduce the soot emission [4,[5][6][7][8][9]. In addition, n-butanol can also be adopted as a single alternative fuel [10][11][12][13][14]. It is indicated that the n-butanol PPC combustion has the potential to obtain low NOx and soot emissions, as well as high thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, many engine workers have researched the influence of fuel injection parameters on the engine combustion and emission, [26][27][28][29] and a lot of deep and valuable results have been revealed. But there is relatively little research about the particle emission characteristics of GDI engines.…”
Section: Introductionmentioning
confidence: 99%